2014
DOI: 10.1590/0102-311x00167512
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns associated with anthropometric indicators of abdominal fat in adults

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2
11

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 24 publications
1
27
2
11
Order By: Relevance
“…Although some epidemiological investigations have shown a significant increase in the sale of ultraprocessed products, which between 2000 and 2013 increased by 43.7% worldwide [23,24], the traditional pattern was the most representative of our population. It includes food items similar to those studies conducted by Gutiérrez-Pliego et al [3] and Vilela et al [6], from Spain and Brazil, respectively, who named them as prudent, and McEvoy et al [25], who investigated diet patterns in several European countries and named them as healthy.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Although some epidemiological investigations have shown a significant increase in the sale of ultraprocessed products, which between 2000 and 2013 increased by 43.7% worldwide [23,24], the traditional pattern was the most representative of our population. It includes food items similar to those studies conducted by Gutiérrez-Pliego et al [3] and Vilela et al [6], from Spain and Brazil, respectively, who named them as prudent, and McEvoy et al [25], who investigated diet patterns in several European countries and named them as healthy.…”
Section: Discussionmentioning
confidence: 94%
“…Vilela et al [6] found an unexpected positive association between the traditional dietary patterns and abdominal adiposity. However, the authors mention that this dietary patterns named as traditional included typical foods of the region, with high energy density, which may Olinto et al [32], in a cohort study with adults carried out in Pelotas, Rio Grande do Sul, Brazil, found significant inverse associations between the scores of the upper quartiles of the Brazilian common dietary pattern considered as healthy and abdominal adiposity represented by the waist circumference.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…35 According to Vilela et al, 36 food choices are extremely important to proper growth and development because the quality and quantity of food ingested interferes with the supply of nutrients and nutritional status. The food consumption profile of the group under study was characterized by frequent intake of foods considered as traditional, such as "rice and beans," which is typical of the Brazilian culture, as well as other fundamental foods for appropriate child growth and development, such as milk and dairy products and red meat, which are important sources of protein, in addition fruits, which are sources of essential vitamins and minerals.…”
Section: Discussionmentioning
confidence: 99%
“…18 On the other hand, studies show that the frequent consumption (three times per week) of fruits and vegetables showed a protective effect in the development of overweight and obesity, considering children between 5 and 9 years. 43,44 For some authors, 36,45 the study of the diet with various combinations of food rather than the consumption of individual food items or the intake of nutrients may be of greater interest, considering that foods are not consumed in isolation and reflect each individual's choice for a particular lifestyle.…”
Section: Discussionmentioning
confidence: 99%